Yankee yarns : storytelling and the invention of the national body in nineteenth-century American culture - Schäfer, Stefanie, Dr (Edinburgh critical studies in Atlantic literatures and cultures., 2021)
A systematic study of the most iconic national character in the US in nineteenth-century literature and culture.